Pedagogical Innovations in Teaching Ethnic Folk Dance in Chinese Higher Education - Yangyang, Lyu; Mee Mee, Rita Wong (Journal of Neonatal Surgery, 2025)
Ethnic folk dance holds significant cultural and educational value in China, representing the diversity and richness of its multi-ethnic heritage. However, traditional pedagogical methods often fail to engage modern students or align with evolving higher education goals. This paper investigates pedagogical innovations in the teaching of ethnic folk dance within Chinese universities, highlighting emerging practices, interdisciplinary approaches, and technology integration. Drawing on case studies, interviews with dance educators, and curriculum analysis, this research identifies key strategies that enhance student engagement, cultural understanding, and creative expression. The findings advocate for a dynamic, student-centered approach that honors cultural authenticity while embracing contemporary educational tools